Psychological biases abilities on constructing weekend anomaly - Brahmana, Rayenda; Hooy, Chee-Wooi; Zamri, Ahmad (Social Science Research Network, 2011)
Even though many researchers have proposed trading behavior as the explanation of the Monday Irrationality or Day-of-the Week anomaly, yet, it has still left without empirical evidence. This research aims to investigate empirically by gauging psychological approach whereas the affection bias (weather-induced mood, and moon-induced mood), and cognition bias (attention bias, and cognitive dissonance) are the factors. Our results report that investor’s Monday irrationality is caused by those psychological biases. Employing one traditional dummy interaction model and an innovation model with market index returns and size-based portfolio returns as our constructs, we found the psychological biases are the explanations beyond the DOWA over the period of 1 January 1999 until 22 March 2010. This research found size does matter in this case as the intuitive judgment of investor plays role on investment decision. Our findings support the conclusion that psychology of investor does play important role on investment decision and resulting DOWA.